Tingkat Pengetahuan, Sikap, dan Dukungan Atasan tentang Pemberian ASI Eksklusif pada Tenaga Kesehatan dan Non Kesehatan - Fitriyani Wijayanti; Ani Margawati; Mohammad Zen Rahfiludin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study compares the knowledge, attitudes, and support from superiors between health and non-health workers at RSUP Dr. Kariadi. The method used is a non-experimental quantitative design with a cross-sectional approach. The research results showed that the majority of respondents in both groups were successful in providing exclusive breastfeeding. The level of knowledge among health workers is better. Supportive attitudes are 57.8% for health workers and 46.7% for non-health workers, and support from superiors in both groups of respondents shows good support. The results of different tests in the two groups show differences in knowledge (p=0.015) and attitudes (p=0.038) regarding exclusive breastfeeding between health and non-health workers. At the same time, in the superior support variable (p=0.053), there is no significant difference between health and non-health workers. Conclusion: There are differences in knowledge and attitudes between health and non-health workers that can influence mothers' decisions about breastfeeding; good superior support can motivate mothers to continue expressing breast milk. Keywords: Superior Support, Exclusive Breastfeeding, Knowledge, Attitude, Health Workers